A dimensão afetiva nas práticas pedagógicas de professoras alfabetizadoras dos anos iniciais do ensino fundamental - Andrade, Milena Andrea Pedral Vanin de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Many factors may contribute to the success or failure of a teaching process, among them, the affective one. This qualitative descriptive research, based mainly on Wallon, Gimeno Sacristán e Leite e Tassoni, had as aims: a) to analyze the conception of affectivity present in the theoretical bases above mentioned; b) to investigate the way the affective dimension is configured in the pedagogical practices of teachers working in the first grades of elementary school.The methodology included the observation of the school routine of two groups of students belonging to the second grade of a public school in Araraquara-SP, Brazil, to identify the way the affective aspects revealed themselves in the teachers' pedagogical practices. We also interviewed both teachers to clarify some aspects of the observation as well as to get some information about their conceptions of affectivity and its importance in the teacher-student relationship. Some results may be appointed: a) the conception of affectivity of both teachers was only partially similar, hence originating some differences in the teacher-student relationship; b) both give support to the students during the class activities, guiding, encouraging, clarifying doubts; c) there are some differences in the evaluation (individual or collective) of the students'activities in the classroom; d) both teachers show concern with the students' learning and always consider their previous knowledge as a starting point to introduce new subjects ; e) the teachers respect the students, both taking into account their individual differences and stimulating those who presented more difficulty, as well as not showing any prejudice in relation to their linguistic variety, different from the school variety; f) both teachers encourage the well succeeded tasks using rewarding words, facial expression and approval gestures. We may conclude that the affective component is fundamental, together with the cognitive ...

Muitos fatores podem contribuir para o sucesso ou o fracasso de um processo de ensino, dentre eles, o afetivo. A presente pesquisa qualitativa, de natureza descritiva, com base principalmente em Wallon, Gimeno Sacristán e Leite e Tassoni, teve como objetivos: a) analisar a concepção de afetividade presente nos referenciais teóricos indicados; b) investigar o modo como se configura a dimensão afetiva nas práticas pedagógicas de professoras alfabetizadoras dos anos iniciais do ensino fundamental. A metodologia compreendeu a observação da rotina escolar de duas classes do segundo ano do Ensino Fundamental de uma escola pública municipal de Araraquara-SP, para identificar como os aspectos afetivos da prática pedagógica docente se configuravam. Foi também realizada uma entrevista com cada uma das duas professoras para esclarecer alguns aspectos da observação bem como conseguir informações sobre suas concepções de afetividade e sua importância na relação professor-aluno. Alguns resultados podem ser apontados: a) as concepções de afetividade das duas professoras são apenas parcialmente semelhantes, daí decorrendo algumas diferenças na interação com os alunos; b) ambas apoiam os alunos durante a realização das atividades pedagógicas, orientando, incentivando, esclarecendo dúvidas; c) há algumas diferenças nas estratégias (individual ou coletiva) de correção das atividades em sala de aula; d) ambas demonstram preocupação com a aprendizagem dos alunos e partem sempre do conhecimento prévio deles na introdução de novos assuntos; e) respeitam o aluno, tanto levando em conta as diferenças individuais e estimulando os que apresentam mais dificuldade, bem como não mostrando preconceito em relação à variante linguística menos culta, diferente da variedade exigida pela escola ; f) ambas elogiam as tarefas bem sucedidas dos alunos por meio de palavras, expressões faciais e gestos de aprovação ...
Keywords: Educação; Afetividade; Professores alfabetizadores; Ensino; Ensino fundamental; Education